COLOR COMBINATION OF ILLUSTRATOR-PAINTER KURIEN MATTHEW: चित्रकार-साजन कुरियन मैथ्यू के चित्रों का रंग संयोजन - Varaulia, Anuradha (International Journal of Research -GRANTHAALAYAH, 2014)
Whatever we see with our eyes in this vrahamana. They first have the effect of color. Many types of colors are found in the universe, most of which are such. Those which the common man can easily identify such as red, yellow, blue, green, purple, black, but apart from these some colors are found. Those which the common man cannot easily identify, colors which cannot be easily detected. Common colors try to know the names of flowers, fruits and vegetables. Mostly such rural areas are heard with individuals. इस व्रम्हंाण में हम अपनी आॅखों से जो भी देखते है। उनमें सबसे पहले रंग का प्रभाव पड़ता है। सृष्टी में अनेक प्रकार के रंग पाये जाते है, जिनमें से अधिकांष रंग ऐसे होते है। जिन्हें आम आदमी आसानी से पहचान सकता है जैसे लाल, पीला, नीला, हरा, बैंगनी, काला, लेकिन इनके अलावा कुछ रंग ऐसे पाये जाते है। जिन्हें आम आदमी आसानी से नहीं पहचान सकता, जिन रंगों को आसानी से नही पहचाना जा सकता है। उन रंगों को आम आदमी फूल, फल एवं सब्जीयों के नाम जानने की कोषिष करते है। अधिकतर ऐसा ग्रामीण क्षेत्र व्यक्तियों के साथ सूनने को मिलता है।